2022
DOI: 10.1002/cbic.202200475
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Dihydroorotate Dehydrogenase Inhibitors Using the Cell Painting Assay

Abstract: Profiling approaches have been increasingly employed for the characterization of disease-relevant phenotypes or compound perturbation as they provide a broad, unbiased view on impaired cellular states. We report that morphological profiling using the cell painting assay (CPA) can detect modulators of de novo pyrimidine biosynthesis and of dihydroorotate dehydrogenase (DHODH) in particular. The CPA can differentiate between impairment of pyrimidine and folate metabolism, which both affect cellular nucleotide po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…CPA identified DCM compound 13 as a potential inhibitor of de novo pyrimidine biosynthesis as it displayed 84% similarity to the pyrimidine synthesis cluster (Figure A–C). As recently reported, this cluster contains modulators of enzymes in pyrimidine biosynthesis like dihydroorotate dehydrogenase (DHODH) and UMP synthase (UMPS) as well as inhibitors of mitochondrial complex III …”
Section: Resultsmentioning
confidence: 99%
“…CPA identified DCM compound 13 as a potential inhibitor of de novo pyrimidine biosynthesis as it displayed 84% similarity to the pyrimidine synthesis cluster (Figure A–C). As recently reported, this cluster contains modulators of enzymes in pyrimidine biosynthesis like dihydroorotate dehydrogenase (DHODH) and UMP synthase (UMPS) as well as inhibitors of mitochondrial complex III …”
Section: Resultsmentioning
confidence: 99%
“…The fingerprints for the compounds with the highest induction value from each of these clusters ( 25 , 15 b , 23 and 20 ) are displayed as heatmap profiles in Figure 3 (Panel C, left). Crucially, pairwise comparison, based on Pearson correlation, revealed that the morphological fingerprints for these compounds have low biosimilarity (Panel C, right) (fingerprints are typically considered similar if biosimilarity >75 % [27] ). These results suggest that our top‐down synthetic approach can deliver sets of screening compounds are functionally (as well as structurally) diverse [28]…”
Section: Resultsmentioning
confidence: 99%
“…High similarities to bioactivity cluster profiles, i. e. >80 %, suggest similar modes of action and thereby facilitate the annotation of uncharacterized compounds without prior knowledge of the top biosimilar reference compounds. So far, 12 bioactivity cluster profiles have been defined that include biological targets related to AKT/PI3K/MTOR, Aurora kinases, BET, DNA synthesis, HDAC, HSP90, Na + /K + ATPases, [36] lysosomotropism/cholesterol homeostasis regulation (LCH), protein synthesis, pyrimidine biosynthesis, [37] tubulin, and uncoupling of the mitochondrial proton gradient.…”
Section: Resultsmentioning
confidence: 99%